Analysis of the Effect of Variations in Wingtip and Winglet Additions of Aeromodelling Aircraft Wings on Flight Performance and Battery Consumption - setiawan, ferry; Putra, Aldi Maha (Langit Biru: Jurnal Ilmiah Aviasi, 2025)
This research develops an aeromodelling aircraft with three wing variations: wingtip, winglet fence, and blended winglet. The aircraft is designed using 3D software and built from polyfoam, with airfoils, servos, ESCs, and motors for control. Each wing type affects performance and battery usage differently. The aircraft is tested over a 5-minute flight. Wingtips improve agility and are the most battery efficient, consuming 12.60%, with battery after Used 87.4%. Winglet fences have similar manoeuvrability to blended winglets but use more battery at 14.32% and 14.61%, respectively. While winglets save energy in large aircraft, in aeromodelling with frequent manoeuvres, they consume more battery due to energy spent on maintaining stability. This study helps aeromodelling enthusiasts choose wings that match their flying needs, whether for agile manoeuvres or fast, straight flight.